2020
DOI: 10.1111/1751-2980.12848
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hepatitis B virus reactivation in patients with hematological malignancies and resolved hepatitis B virus infection: a systematic review and meta‐analysis

Abstract: Objective Patients with resolved hepatitis B virus (HBV) infection are at risk of HBV reactivation during treatment for hematological malignancies. We conducted a systematic review and meta‐analysis of the data on the efficacy of antiviral prophylaxis for the prevention of HBV reactivation in this group of patients. Methods We conducted a systemic literature search of PubMed including MEDLINE and EMBASE databases to 31 January 2019 to identify studies published in English comparing antiviral prophylaxis with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Anti-CD20 monoclonal antibodies rituximab, ofatumumab, and obinutuzumab can cause deep immunosuppression and enhance the HBV reactivation risk in patients with chronic and past HBV infection [29]. In prospective studies of patients with lymphoma receiving anti-CD20 monoclonal antibodies, prophylactic antiviral therapy was associated with a significantly lower risk of HBV reactivation (relative risk 0.17, 95% CI 0.06-0.49, P=0.001) [30].…”
Section: Hbv Reactivation In Patients Receiving B Cell-depleting Drugsmentioning
confidence: 99%
“…Anti-CD20 monoclonal antibodies rituximab, ofatumumab, and obinutuzumab can cause deep immunosuppression and enhance the HBV reactivation risk in patients with chronic and past HBV infection [29]. In prospective studies of patients with lymphoma receiving anti-CD20 monoclonal antibodies, prophylactic antiviral therapy was associated with a significantly lower risk of HBV reactivation (relative risk 0.17, 95% CI 0.06-0.49, P=0.001) [30].…”
Section: Hbv Reactivation In Patients Receiving B Cell-depleting Drugsmentioning
confidence: 99%
“…A meta-analysis including one randomized trial and several observational studies showed a pooled risk estimation of 16.9% reactivation rate (with transaminase elevation and/or detectable HBV DNA) in patients treated with R undergoing the pre-emptive strategy, thus not receiving upfront NAT [13]. In another recent meta-analysis of three prospective studies of patients who received anti-CD20 monoclonal antibodies, the pooled estimated relative risk was 0.17, indicating a significantly lower risk of HBV reactivation in the antiviral prophylaxis group [20]. Finally, in a previous Italian study, only 1 of 85 patients with past HBV infection treated with R-CT and receiving prophylactic LAM showed a serum conversion of HBsAg [19].…”
Section: Introductionmentioning
confidence: 99%
“…chronic hepatitis B or C virus (HBV or HCV), cirrhosis, are the major risk factors for PLC. In China, 80% to 90% of PLC is associated with chronic HBV or HCV infection [3,4].…”
Section: Introductionmentioning
confidence: 99%